2010
DOI: 10.1103/physreva.81.013817
|View full text |Cite
|
Sign up to set email alerts
|

Multifilamentation of powerful optical pulses in silica

Abstract: The multiple filamentation of powerful light pulses in fused silica is numerically investigated for central wavelengths at 355 nm and 1550 nm. We consider different values for beam waist and pulse duration and compare the numerical results with behaviors expected from the plane-wave modulational instability theory. Before the nonlinear focus, the spatiotemporal intensity patterns can be explained in the framework of this theory. Once the clamping intensity is reached, for long input pulse durations (∼1 ps), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…For the fil amentation under these conditions it was shown that the pulse may decay into a quasi periodic sequence of pulses of a few optical periods duration. Comparative analysis of the spatiotemporal stability and multiple filamentation in fused silica for laser pulses at wave lengths that lie in the normal (λ 0 = 355 nm) and anom alous (λ 0 = 1550 nm) GVD regions was made in [38]. The scenarios of spatiotemporal evolution for pulses at these wavelengths were investigated numerically for several values of pulse duration, beam radius, and pulse peak power.…”
Section: Introductionmentioning
confidence: 99%
“…For the fil amentation under these conditions it was shown that the pulse may decay into a quasi periodic sequence of pulses of a few optical periods duration. Comparative analysis of the spatiotemporal stability and multiple filamentation in fused silica for laser pulses at wave lengths that lie in the normal (λ 0 = 355 nm) and anom alous (λ 0 = 1550 nm) GVD regions was made in [38]. The scenarios of spatiotemporal evolution for pulses at these wavelengths were investigated numerically for several values of pulse duration, beam radius, and pulse peak power.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity distributions of multiple filaments emerge in the form of regular or irregular patterns, that are governed by the input beam size, symmetry and smoothness (see, e.g. [140][141][142]). Although the multifilamentation regime creates an illusion of energy scaling of SC, each individual filament is subject to a combined effect of the intensity clamping [60] and the dispersion landscape of the material [61,62], hence no additional spectral broadening with increasing the input power is achieved.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…In a similar way, in our filament, the pulse maintains several temporal slices with sufficient optical power to induce aperiodic recurrent focusing or refocusing events according to the dynamic spatial replenishment model [51] (in contrast to existing periodic solutions mentioned above). As individual time slices refocus, they propagate quasistationary along a distance of some millimeters and are temporally compressed and shifted towards the trailing pulse edge due to the interplay of self-steepening and anomalous dispersion [44]. Every time the corresponding spectral broadening exhibits an overlap to a phase-matched component, a pronounced emission of resonant radiation takes place [ Fig.…”
mentioning
confidence: 99%
“…According to Ref. [44], curves of constant exponential MI gain in the ðk ⊥ ; ωÞ plane are defined by…”
mentioning
confidence: 99%
See 1 more Smart Citation